Description of the Death of Julian the Apostate in Some Christian and Non-Christian Literary Sources (IV-V Century) - Piechocka-Kłos, Maria (Studia Warmińskie, 2014)
This paper presents the description of death of Flavius Claudius Julian (Flavius Claudius Julianus, 361-363), named by later Christian writers “the Apostate”. The description was taken from selected Christian and non-Christian literary sources originating mainly from IV and V century. Leitmotiv for the research were the circumstances of the Emperor’s death and the attempt to identify the killer. The most important sources for this period chosen by the author to familiarize herself with the subject, were: Speech for the Julian glory (Mowa na cześć Juliana) and Speech in the defence of temples (Mowa w obronie świątyń) by Libanus of Antioch (314-395), History of Church by Socrates of Constantinople (ca. 380-450), History of Church by Sozomen (ca. 400-450) and History of Armenia by Faustus of Byzantium (IV/V century). In these writings concerning the death of Julian the Apostate, facts are mixed with legends – the sudden death of the Emperor at the hands of an unknown perpetrator during his Persian campaign, was more than enough to provoke speculation and legends.